Complement-derived chemotactic activity is generated in human serum containing uroporphyrin after irradiation with 405 nm light. - Lim, H W (1981)
Patients with porphyrias have varying degrees of photosensitivity, associated with elevated levels of porphyrins in plasma, erythrocyte, urine and/or feces. To investigate the role of complement in the pathogenesis of cutaneous lesions, varying amounts of uroporphyrin were added to normal human serum (0.1-10 microgram/ml), and the mixtures were then exposed to 405 nm irradiation. Such treatments result in the diminution of total hemolytic complement activity and hemolytic titers of C1, C4, C2, C3, and C5; furthermore, cleavage products of C3 and C5 were detected. Chemotactic activity for human polymorphonuclear leukocytes was generated that was inhibitable by incubation with anti-C5, but not with anti-C3 antisera. No chemotactic activity was generated in Mg++-EGTA treated serum nor in C4-deficient guinea pig serum. These data indicate that irradiation with 405 nm light of normal human serum containing uroporphyrin results in activation of the complement system via the classical pathway, and the generation of complement (C5)-derived chemotactic activity for human polymorphonuclear leukocytes.